The catalyst role of school architecture in enhancing children's environmental behavior - Izadpanahi, Parisa; Elkadi, Hisham (2014)
The interrelationships between school design and children learning are well established. Less evident is the relationship between sustainable school design and the level of environmental behaviour of the children in attendance. Newly erected primary schools in Australia have been broadly graded as either sustainable or conventional. This paper evaluates the impact of both sustainable and conventional school design on children’s environmental behaviour, and examines the correlation between school design and children’s environmental behaviour. 624 children, aged 10-12 years old, completed a survey. This sample, from seven selected primary schools in Victoria (Australia), includes four conventional schools and three sustainable ones. The survey was developed according to GEB (General Ecological Behavior) scale and a few more school specific variables. The outcome of the survey was analyzed using an independent sample t-test and two-way between groups ANOVA in order to assess environmental behavior differences of children in both sustainable and conventional schools taking into account factors that either explicitly and/or implicitly impact on their behavior such as sustainable school design, teachers’ environmental behavior and parents’ environmental behavior. The results show statistically significant differences in environmental behavior of children in sustainable schools and those in conventional schools. Comparing the means of children’s environmental behavior indicates that children in sustainable schools posses higher levels of pro-environmental behavior than children in conventional schools. The paper highlights the strong relationships between school design and children’s environmental behavior, and expands recognition of the role of environmentally sensitive school design not only to improve learning environments but more specifically to engage children ecologically with their immediate built environment.